The Role of Islamic Legal Regulations in Enhancing the Competitiveness of the Halal Tourism Industry in Central Java - Al-Kasyaf, Muhammad Zheeva; Marier, Syauqie Muhammad; Adinugraha, Hendri Hermawan (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This research aims to analyze the role of Islamic legal regulation in enhancing the competitiveness of the halal tourism industry in Central Java, particularly considering the lack of a formal legal framework governing Sharia-based tourism services and destinations. This study is motivated by Central Java’s low position in the National Halal Tourism Index despite its strong potential in Islamic history and culture. A qualitative approach with a case study method was applied in five selected areas: Demak, Kudus, Magelang, Surakarta, and Semarang. Data were obtained through in-depth interviews, field observations, and policy documents analysis. The results show that the absence of specific regional regulations on halal tourism has led to weak service standardization, limited involvement of the Indonesian Ulema Council (MUI), and inconsistencies in application of fiqh mu’amalah principles. The study finds that Islamic legal regulations positively influence the competitiveness of halal destinations by increasing Muslim tourists’ trust, improving the quality of halal infrastructure, and promoting Sharia value-based competitive differentiation. The theoretical implications emphasize the integration of Maqashid Sharia and regional competitiveness theory as a comprehensive framework. This research contributes to Islamic public policy by encouraging collaboration among local governments, fatwa institutions, and industry players in building sustainable halal tourism.